2015
DOI: 10.1164/rccm.201412-2256oc
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antibody-mediated Protection and Defective IgA B-Cell Memory in Experimental Infection of Adults with Respiratory Syncytial Virus

Abstract: Rationale: Despite relative antigenic stability, respiratory syncytial virus (RSV) reinfects throughout life. After more than 40 years of research, no effective human vaccine exists and correlates of protection remain poorly defined. Most current vaccine candidates seek to induce high levels of RSV-specific serum neutralizing antibodies, which are associated with reduced RSV-related hospitalization rates in observational studies but may not actually prevent infection.Objectives: To characterize correlates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
279
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(303 citation statements)
references
References 49 publications
17
279
1
6
Order By: Relevance
“…51 Experimental challenges in healthy adults have shown that serum and nasal IgA titers increase after infection but those levels are poorly maintained. 47 Similar results have been reported for neutralizing antibodies levels in a birth cohort followed-up over three hRSV epidemics. 52 These antecedents suggest that acute production of short-life antibody-secreting cells (ACS) is not impaired.…”
Section: The Humoral Response Against Hrsv Infectionsupporting
confidence: 81%
See 3 more Smart Citations
“…51 Experimental challenges in healthy adults have shown that serum and nasal IgA titers increase after infection but those levels are poorly maintained. 47 Similar results have been reported for neutralizing antibodies levels in a birth cohort followed-up over three hRSV epidemics. 52 These antecedents suggest that acute production of short-life antibody-secreting cells (ACS) is not impaired.…”
Section: The Humoral Response Against Hrsv Infectionsupporting
confidence: 81%
“…46 Similar correlation have been obtained for nasal IgA levels in naturally infection and in experimental challenges in healthy adults. 47,48 On the other hand, it has been described in mice that antibodies play a major role during reinfection, even more than in the first infection, giving a principal role to T cells in the clearance of the virus during the first hRSV challenge. 49 Interestingly, prophylactic treatment with Palivizumab reduces severe hRSV-mediated LRTI, 42,50 and consequently diminish hRSV-associated hospitalization of premature infants, children with congenital heart disease (CHD) and children with cystic fibrosis (CF), 50 suggesting that a neutralizing antibody of high affinity and titer is enough to confer a clinical protection against hRSV disease.…”
Section: The Humoral Response Against Hrsv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous observational studies indicated that local RSV-specific antibodies might be better correlates of protection but suggested that protective antibody levels were not well maintained [40,41]. To address these questions, we used the experimental human infection system to study the relationship between pre-existing local and systemic antibodies with infection [42]. No selection of subjects was made on the basis of pre-existing antibody levels and, among these highly immunologically experienced individuals, approximately 56% become infected following experimental challenge.…”
Section: Experimental Challenge Provides Insights Into Pathogenesismentioning
confidence: 99%